Evaluación comparativa de tres variedades de remolacha (Beta vulgaris L.) en sustrato potencializado con em – biol, mediante sistema organopónico - Martínez Manzo, Angela Irene (2016)
VIII. SUMMARY This work was done on the grounds of the Experimental Farm "San Pablo" of the Faculty of Agricultural Sciences at the Technical University of Babahoyo, located at km. 7.5 of Babahoyo Montalvo route. Geographical coordinates are 79 ° 32 ', west longitude and south latitude 49' 1. This area has a humid tropical climate with an average annual temperature of 25.80 C, an annual rainfall of 2203.8 mm, 79.6% relative humidity, evaporation of 1738.7 mm and a height of 8 m.s.n.m. The floor is flat topography, clay loam texture and regulate drainage. As planting material being treatments beet seed, varieties Crosby egyptian, Detroit Dark Red and Early Wonder and subtratamientos as substrates potentiated with Effective Microorganisms used - Biol, with doses of 100 cc + 250 cc; 100 cc 200 cc +; 100 cc + 150 cc / L H2O, whose experimental design was split plot with three treatments three subtratamientos and three repetitions. The comparisons of means were performed using the Tukey test at 95% probability. all agricultural work required in cultivation for normal development, such as construction of the drawers, placing the substrate, planting, irrigation, fertilization, phytosanitary controls, weed control and harvesting were performed. To determine the effects of treatments and subtratamientos data to the emergency days, plant height, equatorial and polar diameter root length, average weight of five roots, performance and economic analysis were evaluated. According to the results presented was determined that good results were achieved in the comparative study of three varieties of beet with potentiated substrate interacted with MS - Biol, by organopónico system; Detroit Dark Red variety Applying EM - Biol (100 cc + 250 cc / L H2O) emerged more time; the tallest plants Crosby introduced the egyptian variety with applications MS - Biol in doses of 100 cc + 250 cc / L H2O; the equatorial and polar diameter root length got better averages in Crosby variety Egyptian using EM - Biol in doses of 100 cc + 250 cc / L H2O and the best weight of 5 roots, performance and economic analysis was reached in Crosby Egyptian variety, with applications MS - Biol in doses of 100 cc + 250 cc / L H2O, with a net profit of $ 3567.93